Pelatihan Pengenalan Financial Technology (Fintech) Bagi Mahasiswa Peserta Program Pembinaan Mahasiswa Wirausaha (P2MW) Kemendikbudristek - Dani, Rian; Marsyaf, Agesha; Wiarta, Iqra; Hierdawati, Trie (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
This PKM activity was carried out at the Muhammadiyah University of Jambi in the form of material presentations or lectures and discussions regarding the Introduction to Financial Technology (FinTech). In this PKM activity, Rian Dani, M.E., Dr. Agesha Marsyaf and Iqra Wiarta, M.M. act as Speaker. Participants in this PKM activity are students who have passed the 2023 Entrepreneurial Student Development Program (P2MW). The method used in this training is the Lecture Method. The lecture method is a method where the trainer verbally describes or explains to the training participants. Participants have an understanding of Financial Technology (FinTech) such as Crowdfunding, Microfinancing, P2P Lending Service, Market Comparison and Digital Payment Systems. This is marked by an understanding discussion and questions and answers conducted between the participants and the presenters.